Cinéma et lien : une enquête intime auprès d'une famille italienne en Lorraine - Marion Froger; Émilie Tullio (Conserveries Mémorielles)
For the past ten years, two French researchers – Fabrice Montebello et Jean-Marc Leveratto - have been taking an interest in the relations between workers of Italian origins living in Lorraine and cinema, as well as the social practices which derive from them. Our article will consist of continuing their research by interviewing members of the same family whose culture is essentially audiovisual in order to re-create their memory as spectators and as members of the Italian community from the 70's to the present. Research on the diasporas underlines the strong connection existing between the experience of migration and how migrants emotionally respond to their host country. Our hypothesis would thus be that the family's cinematographic experience is closely related to their migrants' history – be it directly or indirectly lived. Hence, cinema appears to be an imaginary space of mediation where migrants can experience in a less painful way the social inadequency they can feel in real life. Moreover, cinema can be seen as an ideal and useful source of information for migrants since it often portrays the new manners and social habits of the host country. But it can also give migrants the opportunity to ponder on moral issues of a universal kind. Cross-cultural experiences often shake the foundation of the migrants' values, yet cinema makes it possible to overcome this state of alienation since every film stimulates ethical reflection – and thus the search for justice – by creating a sense of universal solidarity. The interviews have been done by a member of the family while she was studying in Canada. By accepting to participate in the project, the family proved how important it was for them to pass on their personal and authentic experience. This last remark leads us to our final point: cinema could also be considered as an experience of imaginary sociability – which is closely linked to the experience of social disruption. Moreover, it can make one relive emotions one may have once felt in the past or still feels, and makes it possible to share them with others – especially with the ones we cherish – and experience a kind of mute understanding while watching a movie with them.